Hubungan Pengetahuan Gizi dengan Kesadaran Penerapan Gizi Seimbang pada Remaja di SMA Swasta Kartika 1-2 Medan - Wiwien Ellora Ester Riang Harefa; Rokhiyatul Maila Putri; Fadhilah Setyorini; Donna Permata Sari (Institut Nalanda, 2026)
Awareness of implementing balanced nutrition principles among adolescents is influenced by various factors, one of which is nutritional knowledge. Adequate understanding of balanced nutrition can assist adolescents in making appropriate food choices and adopting healthy lifestyle behaviors. This study aimed to determine the relationship between nutritional knowledge and awareness of balanced nutrition practices among students at Kartika 1-2 Private Senior High School, Medan. The study employed a quantitative approach with an analytical observational design using a cross-sectional method. The sample was selected through proportional random sampling. Data were collected using questionnaires that assessed nutritional knowledge and awareness of balanced nutrition practices. The collected data were analyzed using univariate and bivariate analyses with the Chi-Square test at a 95% confidence level. The findings revealed that most respondents had good nutritional knowledge and a high level of awareness regarding balanced nutrition practices. Statistical analysis indicated a significant relationship between nutritional knowledge and awareness of balanced nutrition practices among adolescents (p < 0.05). These findings suggest that increased nutritional knowledge contributes to greater awareness among adolescents in applying balanced nutrition principles in their daily lives. Continuous nutrition education programs in schools should be strengthened as a strategy to promote healthy behaviors among adolescents. The results of this study are expected to provide valuable information for developing nutrition education and health promotion programs targeting senior high school students.